2016
DOI: 10.1016/j.rmed.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective pilot study examining the use of Acthar gel in sarcoidosis patients

Abstract: In this group of advanced sarcoidosis patients, Acthar gel treatment for at least three months was associated with objective improvement in a third of patients. A third of patients were unable to take at least a three months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 30 publications
1
46
1
Order By: Relevance
“…2). It has been previously noted that RCI was associated with reduction of prednisone in most patients who remained on drug for more than 3 months [8]. We were unable to demonstrate that the reduction in prednisone dosage during the short course of this study was associated with lessening of the toxicities associated with high-dose prednisone such as weight gain and diabetes.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…2). It has been previously noted that RCI was associated with reduction of prednisone in most patients who remained on drug for more than 3 months [8]. We were unable to demonstrate that the reduction in prednisone dosage during the short course of this study was associated with lessening of the toxicities associated with high-dose prednisone such as weight gain and diabetes.…”
Section: Discussioncontrasting
confidence: 59%
“…Studies in infantile spasticity, renal disease, and multiple sclerosis have suggested that the stimulation of these melanocortin receptors may be an important mechanism of action [1922]. Recent experience with using RCI for advanced sarcoidosis has suggested benefit for some patients with sarcoidosis [8, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective series in pulmonary sarcoidosis, ACTHAR gel effected improvements in 11/29 (38%) patients, and allowed >50% prednisone dose reduction in an additional 16 (55%) patients. However, nearly 40% of treated patients were unable to continue the medication, mostly due to side effects [20]. Although ACTHAR gel, a mixture of pituitary extracts including mainly ACTH, activates endogenous cortisol production, it is likely that its effects may also involve nonglucocorticoid receptor mediated pathways.…”
Section: Acthar Gelmentioning
confidence: 99%
“…There have been few contemporary reports of the use of RCI for sarcoidosis [16,17], and only minimal information is available on the dosage and toxicity of RCI in treating patients with chronic sarcoidosis. The product labelling includes little guidance on dosing or the management of common and important adverse effects, leaving physicians who manage sarcoidosis with relatively little direction on the practical use of RCI.…”
Section: Introductionmentioning
confidence: 99%